Hazelnut (Corylus avellana L.) kernels as a source of antioxidants and their potential in relation to other nuts - Delgado, Teresa (2010)
The present work evaluates the potential of hazelnut kernels as a source of antioxidants to be incorporated into new products. First, the effects of extraction conditions on the isolation of hazelnut kernels’ total phenols and antioxidants were evaluated. Six conditions, involving different solvents (water, methanol and aqueous acetone) and contact times, were studied. The highest total phenol contents were obtained with boiling water for 30 min, 44.3±7.7mgGAE/gextract, and 80% (v/v) aqueous acetone solution for 24 h, 36.2±8.8mgGAE/gextract. Increasing the contact time for the acetonic extractions did not improve the total phenols content. Regarding antioxidant activity, the highest DPPH-scavenging effect value was obtained with 80% (v/v) aqueous acetone for 24 h with an effective concentration (EC50) equal to 1.12±0.07 mg/mL. When other nuts – walnuts, almonds, pine nuts and peanuts – were extracted under this condition, only walnut extract exhibited higher phenol content (268±32mgGAE/gextract), antioxidant activity as measured by reducing power (EC50 = 0.091±0.015 mg/mL) and free radical scavenging capacity (DPPH assay) (EC50 = 0.060±0.010 mg/mL) than hazelnut extract. The present work demonstrates that some nuts might be a natural source of bioactive compounds that can be incorporated into new health-related products or be substitutes of synthetic compounds of questionable safety, promoting human health and reducing disease risks.